THE ROLE OF THE MEDIA IN COVERING THE TOURISM CAPACITY: OPPORTUNITIES AND PROSPECTS - Asqaraliyev Saidali Raxmonaliyevich (European Science Publishing, 2026)
This article analyzes the role of the media (media) in covering the tourism potential of Uzbekistan. The research question is: How does the media affect the effective coverage of the tourism potential of Uzbekistan and what opportunities and prospects exist in this process? As tourism becomes one of the important sectors of the economy, the importance of the media in promoting it is increasing. The research was based on qualitative analysis methods and content analysis. Although travel journalism is a major field, it was found that there is almost no modern research on this topic. It is necessary to continue research in order for scientists to continue their research and find solutions to existing problems. According to the results, the field of journalism is an important tool in popularizing tourism, and it was found that multimedia content created in particular on online platforms and social networks is increasing interest in tourism.
Keywords: Tourism, media, media strategy, content analysis, domestic tourism, social networks.